Impact of droop and scarf on the aerodynamic performance of compact aero-engine nacelles - Tejero, Fernando; MacManus, David G.; Sheaf, Christopher T. (American Institute of Aeronautics and Astronautics (AIAA), 2020)
Future turbofan engines will operate with larger engine bypass-ratios and lower specific thrust than current in-service architectures to reduce the specific fuel consumption. This will be achieved by increasing the fan diameter which will incur in an increment in nacelle size and a concomitant larger nacelle drag, weight and interaction effects with the airframe. Therefore, it is required to design compact nacelles which will not counteract the benefits obtained from the new engine cycles. Nacelle design is based on a set of aero-lines that in combination with droop and scarf result in a 3D design. Traditionally, this process was performed by the design of axisymmetric aero-lines. Nevertheless, there is an emerging need to carry out the design process for full 3D configurations to have a better understanding of the effect of droop and scarf angles on the nacelle drag characteristics. This paper presents a numerical method for the multi-objective optimisation of drooped and scarfed non-axisymmetric nacelle aero-engines. It uses intuitive Class Shape Tranformations (iCSTs) for the aero-engine geometry definition, multi-point aerodynamic simulation, a near-field nacelle drag extraction method and the NSGA-II genetic algorithm. The process has been employed to perform independent multi-objective optimisations of compact architectures at selected droop and scarf angle combinations. The multi-objective optimisation framework was successfully demonstrated for the new nacelle design challenge and the overall system was shown to enable the identification of the effects of droop and scarf on compact aero-engines. The proposed tool complements a set of technologies for the design, analysis and optimisation of future civil turbofans aiming at reduction of specific fuel consumption.